DANA PUNIA SEBAGAI SUMBANGAN KEAGAMAAN UMAT HINDU LOMBOK DARI SISI AKUNTANSI - Ni Putu Ari Aryawati; Nengah Sukendri (Guna Sewaka, 2022)
Punia “donation” fund is a religious contribution of Hindus people which must be done sincerely. Accountability push the management for make the punia funds be accountable and transparent. This study aims to interpret the perspective of the Hindu community in Lombok related to the concept of punia “donation” funds. Based on the philosophy of tat twam asi. This study uses an in-depth interview approach with an interpretive paradigm. The results of this study there is a positive relationship related to community behavior in implementing the punia “donation” fund with the philosophy of tat twan asi adopted by Hindus. The financial report for pura could be accountable and transparent. The implication of this research are the accounting of management punia “donation” funds is more complex